Prevalence of HIV in Blood donors in NWFP - Khan, Zubair; Raziq, Fazal; Aslam, N. (Journal of Postgraduate Medical Institute, 2011)
At blood bank PGMI, LRH Peshawar a study was done on 23278 blood donars ragarding their HIV screening the blood donars incldued were form different areas of NWFP. All of them were healthy and were between the age group; of 18 - 60 years. They included both male and female sexes. They were from different communities among 23378 blood donors only 2 donors were positive for HIV. Both the positive donors were male.